Marketing Innovation Strategy Design to Increase Paper and Packaging Sales with the Blue Ocean Strategy Method: Case Study on Wijaya’s Paper - Wijaya, Tarisna Aditya; Harianto , Eric (Golden Ratio of Data in Summary, 2025)
Paper is an essential product in everyday life, in the last decade there has been a change with significant growth in the use of paper, namely the use of recycled paper with used paper waste materials. The use of used paper waste raw materials is carried out to continue to meet the need for paper; even though we have now entered the digitalization era, it cannot be denied that paper is still an essential need in supporting various daily activities. The use of kraft paper (recycled paper) is more in demand by several packaging manufacturers, apart from its environmentally friendly nature, aesthetic factors, and lower prices. Kraft paper is a favorite in the packaging world. This high opportunity does not align with Wijaya Paper's sales in the last two years (2022-2023). Wijaya Paper experienced a decline in turnover compared to 2019-2021 during the first 3 years of the company's establishment. The occurrence of tight market competition, with the implementation of the Ansoff Matrix strategy, with the implementation of Market Penetration and Cost Leadership, is no longer practical because many new competitors have emerged by offering lower prices with illegal goods, imported goods, and leftover roll goods. Through this study, we will discuss how to achieve cost efficiency using the Blue Ocean Strategy approach by identifying SWOT, Key Success Factor, ERRC, and Canvas Strategy so that it can produce the right innovation design for business entities. The research method used in this study is a qualitative triangulation study with informants consisting of internal management, loyal Wijaya Paper consumers, Wijaya Paper competitors, and experts represented by the Marketing Director of PT Adiprima Suraprinta. The results of this study are the design of marketing strategy innovations using the blue ocean strategy approach to increase paper and packaging sales at Wijaya Paper.